The Relationship of Risk Factors with Preterm Labor at Ummi Bogor Hospital in 2022 - Noor Inayati, Inna; Ineu Martini, Ade (Riviera Publishing, 2024)
Preterm labor causes abnormalities in the baby and perinatal death. The exact cause of preterm labor is not yet known, but maternal and pregnancy risk factors can cause it. This study analyzes the relationship between risk factors and preterm labor at Ummi Bogor Hospital Bogor in 2022. The research method uses an observational analytical design of retrospective case-control design. The population is all mothers at Ummi Bogor Hospital Bogor who gave birth prematurely in 2022, as many as 213 people. Bivariate analysis technique using chi-square test. Respondent characteristics were 64.8% of mothers aged 20-30 years, 60% multipara, 86.9% with singleton pregnancies, 82.2% with HAP, 71.4% with KPD, 75.5% with PEB, and 97.7% with fetal distress. The results of bivariate analysis used che square test of age p values (p = 0.846), p parity (p = 0.161), p game (0.118), p HAP (p = 0.354, p KPD (p = 0.861), p PEB (p = 0.404) and p Fetal distress (p = 0.252). In conclusion, there is no relationship between age, parity, gameli, HAP, KPD, PEB, and fetal stress factors for preterm labor at Ummi Bogor Hospital Bogor in 2022.